A High and Rising Rate of Interest - Hansen, Alvin H. (The Review of Economics and Statistics, 1957)
seems to me much too severe and based in part on a misinterpretation or misunderstanding of the Ricardian doctrines. Knight as a full adherent of the post-I870 revolution in value and distribution theory, or departure from the Ricardian-classical to the utility and marginalist analysis, is I think half blind to the insights, of enduring value, contained in the former and preserved in the Marshallian synthesis. But I cannot, for lack of space, go further into this subject. My final advice to the reader must be: don't rely on this review but read the book!